Handphone Mempengaruhi Terhadap Perilaku Remaja Usia SLTP (13-15 Tahun) Di Dusun Tegalpare Kecamatan Muncar Kabupaten Banyuwangi - Abdul Aziz (IAI Darussalam, 2016)
Advances in communication and information technology such as mobile phones not only hit the people who live in urban areas but can be enjoyed by people in remote villages. People who once so thick with their culture little by little more lost. This research is focused on